Hubungan antara Literasi Perubahan Iklim dan Perilaku Pro-Lingkungan pada Siswa SMA - Adawiyah, Putri Rabiatul; Hidayat, Saifullah; Rofi'ah, Ndzani Latifatur (Universitas Negeri Jakarta, 2025)
Climate change literacy and pro-environmental behaviour have been proven to be one of the solutions to address climate change in the student’s perspective from several countries. Therefore, it is crucial to gain a comprehensive understanding of the relation between these two variables for the impact on climate change in Indonesia. The objective of this research was to analyse the relationship between climate change literacy and pro-environmental behaviour among senior high school students in Indonesia. A correlation study was conducted using a survey method. The samples were students from the X, XI, and XII grades of senior high school, collected using proportionate stratified random sampling. A total of 386 students from three schools participated in this survey. The test comprised a climate change awareness instrument to examine climate change literacy. Furthermore, a questionnaire was used to measure pro-environmental behaviour among high school students. Additionally, interviews were conducted to obtain comprehensive data. The results demonstrated a positive and highly significant relationship between climate change literacy and pro-environmental behaviour among senior high school students. This research highlighted that awareness of climate change causes and government policies related to climate change influenced pro-environmental behaviour.